1976
DOI: 10.1073/pnas.73.11.3928
|View full text |Cite
|
Sign up to set email alerts
|

Negative homotropic cooperativity and affinity heterogeneity: preparation of yeast glyceraldehyde-3-phosphate dehydrogenase with maximal affinity homogeneity.

Abstract: A three-step procedure including affinity chromatography on NAD+-azobenzamidopropyl-Sepharose has been designed for the purification of yeast glyceraldehyde-3-phosphate dehydrogenase [D-glyceraldehyde-3-phosphate: NAD+ oxidoreductase (phosphorylating), EC 1.2.1.12] with maximized specific activity and maximized homogeneity with respect to affinity for the coenzyme, NAD+. Binding isotherms allow the analysis of cooperativity patterns that disclose both the average ligand affinity in the system and the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, the finding that symmetry can be preserved even during sequential filling of binding sites indicates the applicability of the symmetry principles of the MWC model to negative cooperativity, which its authors did not anticipate. At the time of the MWC model most cases of negative cooperativity were regarded as artifacts resulting from partial protein activity, as was later verified [44] for the controversial case of apparent negative cooperativity that had led to elaboration of the sequential allostery model [45]. Since that time, however, many carefully-documented examples of negative cooperativity including ArgR establish beyond doubt that both positive and negative cooperativity are common molecular strategies that serve complementary physiological purposes.…”
Section: Resultsmentioning
confidence: 98%
“…However, the finding that symmetry can be preserved even during sequential filling of binding sites indicates the applicability of the symmetry principles of the MWC model to negative cooperativity, which its authors did not anticipate. At the time of the MWC model most cases of negative cooperativity were regarded as artifacts resulting from partial protein activity, as was later verified [44] for the controversial case of apparent negative cooperativity that had led to elaboration of the sequential allostery model [45]. Since that time, however, many carefully-documented examples of negative cooperativity including ArgR establish beyond doubt that both positive and negative cooperativity are common molecular strategies that serve complementary physiological purposes.…”
Section: Resultsmentioning
confidence: 98%
“…Implicit in the foregoing is the assumption that the enzyme preparation is homogeneous. Slade has found that heterogeneity with respect to NAD affinity exists in yeast glyceraldehyde-3-phosphate dehydrogenase which is in other respects homogeneous (Gennis, 1976). On the other hand, the reordered alkylation experiment of Stallcup & Koshland (1973a) indicates that heterogeneity does not contribute to the half-of-the-sites reactivity that they observe in this enzyme.…”
Section: Discussionmentioning
confidence: 96%